A Canadian Clinical Practice Algorithm for the Management of Patients with Non-Variceal Upper Gastrointestinal Bleeding. (1st October 2004) - Barkun, Alan; Fallone, Carlo A; Chiba, Naoki; Fishman, Marty; Flook, Nigel; Martin, Janet; Rostom, Alaa; Taylor, Anthony; for the Nonvariceal Upper GI Bleeding Consensus Conference Group,
Abstract : AIM: To use current evidence-based recommendations to provide a user-friendly clinical algorithm for the management of upper gastrointestinal bleeding, adapted to the Canadian environment. METHODS: A multidisciplinary consensus group of 25 participants representing 11 national societies used a seven-step approach to develop recommendations according to accepted standards. Sources of data included narrative and systematic reviews as well as published and new meta-analyses. A small writing subgroup subsequently created the algorithm. RESULTS: Recommendations emphasize appropriate initial resuscitation of the patient and a multidisciplinary approach to clinical risk stratification that determines the need for early endoscopy. Early endoscopy allows safe and prompt discharge of selected patients classified as low risk. Endoscopic hemostasis is reserved for patients with high-risk endoscopic lesions. Although monotherapy with injection or thermal coagulation is effective, the combination is superior to either treatment alone. High-dose intravenous proton-pump inhibition is recommended in patients who have undergone successful endoscopic therapy. Routine second-look endoscopy is not recommended. Patients with upper gastrointestinal bleeding secondary to ulcer disease should be tested and treated for Helicobacter pylori infection. CONCLUSIONS: This algorithm should facilitate appropriate risk stratification, use of endoscopic therapy and the appropriate utilization of proton-pump inhibition to optimize the care of patients with upper gastrointestinal bleeding. The algorithm should be customized to the resources of individual medical centres. Its application should be studied with appropriate outcomes recorded and validation performed.